The Effect of Multiple Role Conflicts and Workload on Employee Performance through Work Motivation - Sandra Purwanty; Endang Suswati; G. Budi Wahyono (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives – The purpose of this study was to analyze the effect of multiple role conflicts and workload on work motivation and employee performance and to analyze the effect of multiple role conflicts and workload on employee performance through work motivation. Design/Methodology/Approach – The research respondents were female employees (ASN and NON-ASN) at the Regional Secretariat Office of Mojokerto Regency, totaling 70 people. The research instrument was a questionnaire which was then analyzed with a path test Findings – The results of the study show that multiple role conflicts and workload have proven to influence employee motivation. Multiple role conflicts and workloads are proven to affect employee performance. Motivation is proven to influence employee performance. Multiple role conflict is not proven to indirectly affect employee performance through motivation and workload is proven to indirectly affect employee performance through motivation